Review of the Literature on Determinants of electronic banking adoption by customers - Saxena, Divya (Opción, 2019)
The purpose of this paper is to review the adoption of electronic banking by customers, through a research model tested by the questionnaire as a method, which incorporates customer-related factors. The results show that electronic banking adoption has grown significantly across the world and it has been well studied in the context of developed countries, but in developing and underdeveloped countries still remain fertile for further academic research.Collectively, financial institutions need to make sure that the best features of their e-banking systems are well communicated to potential users in light of the individual differences among their customer segments.